Analysis of mathematics problem-solving ability on plane figure subject based on van hieles theory at Junior High School - Deanti Ramadhania; Sudi Prayitno; Sri Subarinah; Arjudin Arjudin (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram, 2022)
This study aims to describe the ability to solve mathematical problems in Plane Figure Subject based on van Hiele's theory in class VIII students of SMP Negeri 1 Mataram in the academic year 2021/2022. The type of research used is descriptive qualitative, which produces data in the form of written or spoken words from people and observed behavior. The subjects in this study were students in class VIII-E at SMP Negeri 1 Mataram, totaling 36 students. The method of taking the subject in this study used purposive sampling, which was selected based on the objectives to be achieved. The data collection methods used are the van Hiele test and the flat wake problem-solving ability test, interviews, and documentation. The thinking level of students in taking the van Hiele test was: 20 students at level 0 (visualization) with a percentage of 55.56%, 13 students at level 1 (analysis) with a percentage of 36.11%, and 3 students at level 2 (informal deduction) with a percentage of 8.33%. Furthermore, students at each level of van Hiele's thinking were taken as representatives of each of the 2 subjects to carry out a problem-solving ability test. Based on the results of the research on the problem-solving abilities of students based on the Polya problem-solving stage, students who are at level 0 can understand the problem but have not been able to carry out the other Polya-solving stages. Students at level 1 can understand the problem and develop a settlement plan but have not been able to carry out the other stages of Polya solving. Students at the level can understand the problem, develop a settlement plan, and carry out a settlement plan but have not been able to re-examine. It shows that the higher the van Hiele thinking level of the students, the better their problem-solving abilities will be.